Case Report: Recurrent colonic metastasis from lung cancer—diagnostic pitfalls and therapeutic challenge of a peculiar case - Tramontano, Salvatore; Sarno, Gerardo; Prisco, Vera; Tedesco, Anna Mirea; Gargiulo, Antonio; Bracale, Umberto (Frontiers in Surgery, 2023)
Lung cancer (LC) mortality exceeds 20%, and detecting metastases from LC is becoming a challenging step in understanding the real prognostic role of specific localization. We report a case of a patient with lung metastasis to the colon with local recurrence at the anastomosis after radical resection for metastasis. In both cases, the diagnosis was on oncological follow-up, and surgery was offered in consideration of reasonable life expectancy, good control of LC, and high risk of intestinal occlusion. A 67-year-old male, with a history of LC 18 months ago, was referred to our surgical unit after a positron emission tomography CT total body, where an area of intense glucose metabolism (SUV max: 35.6) at the hepatic colic flexure was reported. A colonoscopy revealed an ulcerated, bleeding large neoplasm distally to hepatic flexure, almost causing resulting total occlusion. Histologic examination revealed a tumor with complete wall thickness infiltration, which appears extensively ulcerated, from poorly differentiated squamous carcinoma (G3), not keratinizing, with growth in large solid nests, often centered by central necrosis. Two of the 30 isolated lymph nodes were metastatic. The omental flap and resection margins were free from infiltration. The malignant cells exhibited strong positive immunoreactivity only for p40. The features supported metastatic squamous carcinoma of lung origin rather than primary colorectal adenocarcinoma. After 8 months from surgery, intense Fluorodeoxyglucose (FDG) uptake of tissue was confirmed in the transverse colon. Colonoscopy evidenced an ulcerated substenotic area that involved ileocolic anastomosis on both sides. Reoperation consisted of radical resection of ileocolic anastomosis with local lymphadenectomy and ileotransverse anastomosis. The second histologic examination also revealed poorly differentiated squamous carcinoma (G3), not keratinizing, with positive immunoreactivity only for p40, suggesting the origin of LC. This case report confirmed that the possibility of colonic secondary disease should be part of the differential diagnosis in asymptomatic patients and those with a history of LC diagnosis. In addition, relapse of colonic metastasis is infrequent but should be considered during follow-up of LC. More studies on colonic metastasis of LC are required to better understand the clinical features and outcomes.